Encouraging University–Community Collaboration: Why, How and Towards What End? - Polya Katsamunska; Allan Rosenbaum (Transylvanian Review of Administrative Sciences, 2020)
Increasingly, all throughout the world, universities have begun to initiate activities and projects that go beyond the classroom and which profoundly impact both the communities of which they are a part and society more generally. In order to better understand how such initiatives work to benefit both university and community, we examine two very different projects emerging out of the private and public sectors in Bulgaria and the United States. The analysis is focused on two cases of university activities of quite different types, which impact their respective communities in very different ways. The purpose is to provide a better understanding of both the wide array of activities through which universities interact with their societies and communities, as well as to examine the consequences and benefits to both the institution and the society of such activity. The two projects presented in the article are very different in many respects but, at the same time, they serve to point out the many elements that such projects have in common and the many diverse ways in which they can benefit the institutions carrying them out. They also serve to tie the institutions involved much more closely to the various communities of which they were a part and resulted in significant engagement with those communities by the faculty involved in them.